The serum levels and clinical significance of interleukin-33 and soluble ST2 in patients with vitiligo - Li YANG; Dong-qing LU; Han MA (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To investigate the clinical significance of interleukin-33(IL-33) and soluble ST2 (sST2) in patients with vitiligo. Methods: The serum concentrations of IL-33 and sST2 were determined by enzyme linked immunosorbent assay (ELISA) respectively in 62 patients with vitiligo and 30 healthy controls. The levels of IL-33 and sST2 in patients in different disease stage, clinical course and lesion area were assessed. Results: The expression levels of serum IL-33 and sST2 were higher in peripheral blood of patients in progressive stage and stable stage of vitiligo than those in the normal controls (IL-33: t=4.67, 2.34, P<=0.004, 0.031, respectively; sST2: t=3.59, 2.09, P<=0.027, 0.045, respectively). The level of sST2 in the abnormal autoantibody group of patients with vitiligo was significantly higher than that in the non-abnormal autoantibody group (t=2.46, P<=0.015). There was no significant differences of IL-33 and sST2 for gender, white spot area, family history, mental stress, and clinical microelement (all P>0.05). Serum IL-33 or sST2 did not significantly correlate with age or disease duration in patients with vitiligo (all P>0.05). Conclusions: IL-33 and sST2 may play an important role in the pathogenesis of vitiligo.